Incidência de hérnia interna em pacientes submetidos à cirurgia bariátrica em um hospital privado na cidade de Belém do Pará - OLIVEIRA, André Luís Meireles de (2023)
BACKGROUND: Laparoscopic Roux-en-Y gastric bypass (BGYRL) is one of the most performed procedures worldwide, one of its complications is the internal hernia (HI), presenting a significative and highly variable incidence in the literature (0-16%). So, the objective of this study was to analyze the incidence of internal hernia after BGYRL in a private hospital in the city of Belém, Pará. METHODS: Were revised the records of the patients which were submitted to BGYRL between January/2011 and December/2016 and developed HI in post-operatory diagnosed with laparoscopy. The analytical statistics was utilized to evaluate the results of the categorical variables on the sample through the G test and Pearson’s chi-square test RESULTS: 180 pacients (117 women and 63 men) were submitted to BGYRL at the studied hospital in the stablished period, 16,7% were diagnosed with HI (n=30), demonstrating a higher incidence than was found in the literature. Being 18 females (60%) and 12 males (40%), it wasn’t found statistical significance in the proportion between the sexes (p=0.3613). About the age groups of the patients diagnosed with HI, from 20 to 30 years presented 3 cases (33,3%); 31 to 40 years presented 12 cases (40%); 41 to 50 years presented 10 cases (33,3%); 51 to 60 years presented 5 cases (16,7%). There were no meaningful difference between the age groups (p = 0.0635). The principal site of intestinal herniation found during laparoscopy in patients diagnosed with HI was through Petersen’s space (n=20; 66,7%), there were statistical significance in these group (p=0.0004). Laparoscopy was diagnostic as it was resolutive in 28 patients with HI (p < 0.0001). 29 patients were discharged from hospital (96,67%) and 1 died during hospital internment (3,33%). CONCLUSION: The incidence of HI in patients submitted to BGYRL in the referred hospital is higher than found in the literature. In the majority of the cases the correction of HI was made with success through laparoscopy. There is no consensus in the literature about which would be the principal site of internal herniation. The demographics were not statistically relevant in relation to HI. The conversion rate to laparotomy and the necessity of reoperations practically were not debated in the publicated researches, being necessary more detailed studies to evaluate the importance of these factors in the morbimortality of this pathology. There are few studies about this complication, which is possibly fatal; therefore more researches are necessary, mainly due to the growing number of bariatric surgeries in the last years.